Gambaran Pemeriksaan Hasil HBsAg pada Ibu Hamil Trimester Ii dalam Deteksi Hepatitis B di Banyumas - Auliya Khairin; Ratna Wulandari; Anisa Nur Afdila; Shofia Putri Kawiswara; Cahya Putri Utami; Fatra Guhanda; Fu’ad Minan Zuhri (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Hepatitis B is a viral infection that remains a public health problem, especially in pregnant women due to the risk of vertical transmission of infection to the fetus. Hepatitis B Surface Antigen (HBsAg) examination in pregnant women is necessary as an early detection effort to prevent hepatitis B transmission from mother to baby. This study aims to describe the results of HBsAg examination in second-trimester pregnant women in the detection of hepatitis B in Banyumas. The type of research used is descriptive observational with a cross-sectional approach. The population consisted of secondtrimester pregnant women with a sample of 23 respondents who met the inclusion and exclusion criteria. Venous blood samples were taken and examined using the HBsAg immunochromatography method (strip test). The data obtained were analyzed descriptively qualitatively to describe the results of the HBsAg examination. No second-trimester pregnant women were found with positive HBsAg results in the samples examined. The results showed that all respondents had negative HBsAg test results (100%). It can be concluded that no active hepatitis B virus infection was detected in pregnant women. HBsAg examination using the strip test method can be used as an initial screening method for early detection of hepatitis B in pregnant women. This study shows that the use of strip tests is still recommended for routine HBsAg examinations to prevent transmission of hepatitis B from mother to baby